Evaluation of a revised indication for determining adult cochlear implant candidacy. (24th February 2017) - Sladen, Douglas P.; Gifford, René H.; Haynes, David; Kelsall, David; Benson, Aaron; Lewis, Kristen; Zwolan, Teresa; Fu, Qian‐Jie; Gantz, Bruce; Gilden, Jan; Westerberg, Brian; Gustin, Cindy; et al.
Abstract : Objective: To evaluate the use of monosyllabic word recognition versus sentence recognition to determine candidacy and long‐term benefit for cochlear implantation. Study Design: Prospective multi‐center single‐subject design. Methods: A total of 21 adults aged 18 years and older with bilateral moderate to profound sensorineural hearing loss and low monosyllabic word scores received unilateral cochlear implantation. The consonant‐nucleus‐consonant (CNC) word test was the central measure of pre‐ and postoperative performance. Additional speech understanding tests included the Hearing in Noise Test sentences in quiet and AzBio sentences in +5 dB signal‐to‐noise ratio (SNR). Quality of life (QoL) was measured using the Abbreviated Profile of Hearing Aid Benefit and Health Utilities Index. Results: Performance on sentence recognition reached the ceiling of the test after only 3 months of implant use. In contrast, none of the participants in this study reached a score of 80% on CNC word recognition, even at the 12‐month postoperative test interval. Measures of QoL related to hearing were also significantly improved following implantation. Conclusion: Results of this study demonstrate that monosyllabic words are appropriate for determining preoperative candidate and measuring long‐term postoperative speech recognition performance. Level of Evidence: 2c. Laryngoscope, 127:2368–2374, 2017